Thermal stability of PdGe films on Ge(100) substrate. (15th July 2016) - Toinin, Jacques Perrin; Hoummada, Khalid; Bertoglio, Maxime; Portavoce, Alain
Abstract: The thermal stability of PdGe on Ge(100) was investigated by scanning electron microscopy, X-ray diffraction and atom probe tomography. The initial PdGe film agglomerates when heated at high temperature (≥ 500 °C), forming spherical islands. This degradation is highly detrimental for PdGe ohmic contact fabrication in the Ge-based nano-electronics technology. However, capping the Pd layer with W before Pd-Ge reaction increases the thermal stability of the PdGe film up to 600 °C. In addition, the PdGe texture is modified if the sample is heated during Pd deposition, increasing the thermal stability of PdGe up to 700 °C with the W cap. Graphical abstract: